Effects of proactive and prosocial behavior on critical incidents of Lima schoolchildren - Holguin Alvarez, Jhon A. (2017)
The study focuses on the theoretical approaches of proactive and prosocial behavior of Covey (1996), Xifra (2009) and Roche-Olivar (2004), with the objective of analyzing the significant differences in the decrease of critical incidents in public school students And private schools in the district of San Juan de Lurigancho, for which two experimental workshops with quasiexperimental methodology were applied in three groups of 1st and 2nd high school students (G. Exp. (Proactivity) = 17; G. Exp. Prosociality) = 15; G. Control = 16); A behavior observation log and the PANIC instrument of Monereo and Monte (2011) were used. The results indicate significant differences with better effects in the workshop of proactive behavior (Hrp = 16.59, p <.05); A comparison of the verbal violence dimension in which better effects were obtained by the prosocial behavior workshop (Hrp = 14.12, p <.05); Finally, the limitations were that students in the proactivity workshop slowed down their critical incidents by demonstrating excessive personalism, and for later studies, it is suggested to work the above mentioned workshops, including assaulted students.